2021
DOI: 10.1212/cpj.0000000000000834
|View full text |Cite
|
Sign up to set email alerts
|

Facial Onset Sensory and Motor Neuronopathy

Abstract: Purpose of reviewTo improve our clinical understanding of facial onset sensory and motor neuronopathy (FOSMN).Recent findingsWe identified 29 new cases and 71 literature cases, resulting in a cohort of 100 patients with FOSMN. During follow-up, cognitive and behavioral changes became apparent in 8 patients, suggesting that changes within the spectrum of frontotemporal dementia (FTD) are a part of the natural history of FOSMN. Another new finding was chorea, seen in 6 cases. Despite reports of autoantibodies, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…[2] One hundred cases of FOSMN syndrome have been reported to date. [3] FOSMN syndrome is typically characterized by the onset of facial paresthesia and sensory deficits in the facial trigeminal innervation area, with slow development along the rostral-caudal direction, affecting the scalp, neck, upper trunk, and upper limbs in a gradually progressive manner. [2][3][4][5] At the same time or later than the sensory symptoms, the cranial nerve and upper limb motor disorders also appear slowly, spreading in the same pattern as the sensory disorders.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[2] One hundred cases of FOSMN syndrome have been reported to date. [3] FOSMN syndrome is typically characterized by the onset of facial paresthesia and sensory deficits in the facial trigeminal innervation area, with slow development along the rostral-caudal direction, affecting the scalp, neck, upper trunk, and upper limbs in a gradually progressive manner. [2][3][4][5] At the same time or later than the sensory symptoms, the cranial nerve and upper limb motor disorders also appear slowly, spreading in the same pattern as the sensory disorders.…”
Section: Discussionmentioning
confidence: 99%
“…[3] FOSMN syndrome is typically characterized by the onset of facial paresthesia and sensory deficits in the facial trigeminal innervation area, with slow development along the rostral-caudal direction, affecting the scalp, neck, upper trunk, and upper limbs in a gradually progressive manner. [2][3][4][5] At the same time or later than the sensory symptoms, the cranial nerve and upper limb motor disorders also appear slowly, spreading in the same pattern as the sensory disorders. Clinical symptoms and signs include asymmetric facial paralysis, masseter and temporal muscle weakness, dysarthria, dysphagia, tongue atrophy, and even dyspnea in a few patients, which may eventually lead to respiratory failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only three reported patients have benefited, with only one having long-term effect and the other two patients having only transient improvement. 2,12 Considering the controversial therapeutic effects and the definite side effects of steroids, we did not use immunomodulatory therapies in our patients. It has been reported that the combined use of the ALS-targeted drug riluzole and the anti-inflammatory drug celecoxib presented neuroprotection in FUS-tg mice, which may imply the potential benefits in FOSMN.…”
Section: Discussionmentioning
confidence: 99%
“…Heterozygous mutations in several fALS genes have been reported in FOSMN syndrome, including TARDBP , SOD1 , SQSTM1 , VCP and CHCHD10 , although the pathogenic significance of these remains to be determined. 73 Although the aetiology of FOSMN syndrome remains to be fully elucidated, the identification of TDP-43 positive intraneuronal inclusions suggests that FOSMN syndrome is a neurodegenerative disorder. 74–76 Importantly, some studies have failed to detect TDP-43 inclusions, 72 77 suggesting a heterogeneity of the disease process in FOSMN syndrome.…”
Section: Introductionmentioning
confidence: 99%